Future design of accessibility in games: A design vocabulary. Issue 131 (November 2019) - Cairns, Paul; Power, Christopher; Barlet, Mark; Haynes, Greg
Highlights: A state of the art review of the work in making digital games accessible. An argument for the limitations of current approaches to game accessibility. A proposal to have a design language that is suitable to support games developers to think about how to make their games accessible. An initial vocabulary based on a content analysis of existing guidelines to support the design of accessible games. Abstract: Games represent one of the most significant cultural artefacts of this century. They are a massive force in economies around the world and are enjoyed by millions of players worldwide. With their cultural significance firmly in place, it is important to ensure that all people can participate in and play games in order to feel included in our wider society. For people with disabilities, games in particular provide a cultural outlet where they can be included with everyone else, and enabled to do things on an even footing with their non-disabled peers. However, this only happens if we create the necessary design environments that provide inclusive opportunities to game alongside the rest of the player base. Guidelines have been successful in raising awareness of accessibility in games and still function well for evaluating finished games. However, they are not the generative design thinking tools that developers need. Further in being divided to address specific disabilities, they are not capturing the diversity of needs of players with disabilities and the personalised and idiosyncratic adaptations that they make in order to play. We therefore propose developing a vocabulary and language of game accessibility which is no longer about whether someone can perceive or operate an interactive technology, but instead as to whether they can have the experience they want to have. We propose the structure for such a vocabulary showing that it needs to distinguish between access to controls, enablement to meet the challenges of the game and the player experience itself. We show how the intermediate-level knowledge embodied in guidelines can be reformulated in this way to be more generative and so support designers to develop games that deliver accessible player experiences.